Advanced medical statistics - Lü, Ying; Fang, Ji-Qian 1939- (World Scientific, 2015)
The book aims to provide both comprehensive reviews of the classical methods and an introduction to new developments in medical statistics. The topics range from meta analysis, clinical trial design, causal inference, personalized medicine to machine learning and next generation sequence analysis